Methodology of water quality index (WQI) development for filtrated water using irradiated basic filter elements - Nuraslinda A.; Pauzi A.M.; Bakar A.; Arif A. (American Institute of Physics Inc., 2023)
Clean water production can be achieved by using common simple water filtration system that consists of an empty bottle and the filter elements such as cotton/coffee filter, sands, and gravels, which can be easily assembled and used. To reduce the time to get an acceptably clean water using the common water filtration, this paper will discuss on a solution to increase the filtration effectiveness of the filter elements by irradiating gossypium (or commonly known as cotton), and silica oxide which is the main composition material for sand and gravel from various scale based on the Wentworth scale. There were few studies regarding gamma and neutron irradiation of silica based materials that proves that gamma and neutron irradiation introduce defects, hence, we expect that it may lead to the formation of micropores and alter the water filtration effectiveness. It was established that higher amount of irradiation results in higher concentration of defects. This paper will firstly review literatures on the effect of gamma and neutron irradiation effect on filter elements such as sands and papers, and then develops a water quality index (WQI) that reflects the water appearance quality of the filtrated water. The WQI focuses on the physical appearance such as smells and color of the filtered water.